2007
DOI: 10.1109/tit.2006.890720
|View full text |Cite
|
Sign up to set email alerts
|

Throughput and Delay in Random Wireless Networks With Restricted Mobility

Abstract: Grossglauser and Tse (2001) introduced a mobile random network model where each node moves independently on a unit disk according to a stationary uniform distribution and showed that a throughput of Θ(1) is achievable. El Gamal, Mammen, Prabhakar and Shah (2004) showed that the delay associated with this throughput scales as Θ (n log n), when each node moves according to an independent random walk. In a later work, Diggavi, Grossglauser and Tse (2002) considered a random network on a sphere with a restricted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…There has been some recent interesting work on characterizing the delay performance of scheduling algorithms, or formulating scheduling and routing policies in random networks that attain order-optimal delay [6], [7], [20], [14], [16], [17]. Most of these works do not consider queuing delay, and focus on attaining order-optimal packet delivery delay in presence of node mobility.…”
Section: Related Workmentioning
confidence: 99%
“…There has been some recent interesting work on characterizing the delay performance of scheduling algorithms, or formulating scheduling and routing policies in random networks that attain order-optimal delay [6], [7], [20], [14], [16], [17]. Most of these works do not consider queuing delay, and focus on attaining order-optimal packet delivery delay in presence of node mobility.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, there are some works ( [2], [8], [9], [15], [19], [20]) about the trade-off between capacity and delay in mobile ad hoc networks. They show that by using mobility to increase the capacity of the network, the delay will also be increased.…”
Section: Delay In Hybrid Wireless Network Under L-maximum-hop Resmentioning
confidence: 99%
“…[2], [8], [10], [15], [19], and [20] propose to utilize nodes' mobility to deliver packets. Each packet is only relayed for very few times before arriving at the destination.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Gamal et al [2] showed that the Θ(1) throughput is also achievable under a random walk model, but which comes at the price of a Θ(n log n) delay. Mammen et al [3] proved that the same throughput and delay scaling are also achievable even with a variant of the Grossglauser-Tse 2-hop relay and a restricted mobility model. The delay and throughput trade-off has been further widely studied under different mobility models, like the i.i.d.…”
Section: Introductionmentioning
confidence: 95%